Analysis of Subgradient Extragradient Iterative Schemes for Variational Inequalities. (5th November 2021) - Wu, Danfeng; Zhu, Li-Jun; Shan, Zhuang; Yin, Tzu-Chien
Abstract : In this paper, we investigate the monotone variational inequality in Hilbert spaces. Based on Censor's subgradient extragradient method, we propose two modified subgradient extragradient algorithms with self-adaptive and inertial techniques for finding the solution of the monotone variational inequality in real Hilbert spaces. Strong convergence analysis of the proposed algorithms have been obtained under some mild conditions.